الأحكام الفقهية الخاصة بالمرأة في العبادات والجنايات والحدود )ةنراقم ةيهقف ةسارد(Al-Hikam Al Fiqhiyyah Al Khassah Bi Al Mar'ah Fi Al Ibadat Wa Al Jinayat Wa Al Hudud - Toulait, Redouane; , Dr. M. Muinudinillah Basri, M.A; , Dr. M. Abdul Kholiq Hasan, M.A., M.Ed (2014)
It is a qualitative approach based on quality rather than on quantity, also adopted a researcher on the method of reasoning, where evidence shows the reported provisions of jurisprudential, and have evidence of Book of Allah or of the Sunnah of the Prophet or the sayings of the Ancestors, God bless them all. As well as the method of comparison, after the evidence researcher compares them, and discusses what needs to discuss them, and then shows what swung him from this evidence. The researcher concluded that Allah singled out women with certain provisions that fits Aftrtha and nature, whether in prayer or zakat or hajj or felonies and borders.